A Catholic spirituality for business : the logic of gift - Schlag, Martin, 1964-; Melé, Domènec (The Catholic University of America Press, 2019)
Spirituality and gift are notions that are en vogue. Topics such as spirituality at the workplace, spirituality management, spirituality in leadership, organizational spirituality and other related topics are trending in management literature. The "logic of gift" is also appearing more frequently, especially in attempts to rethink the way our economy works in order to include the marginalized. The expression "logic of gift" was introduced into official Catholic social teaching by Pope Benedict XVI, who presented it in association with the principle of gratuitousness, which in turn is an expression of fraternity. However, beforeCaritas in Veritate and ever since Marcel Mauss's groundbreaking work The Gift, the importance of gift for human relationships and for the cohesion of society had been increasingly recognized. Alain Caillé and Jacques T. Godbout further fleshed out the implication of gift for contemporary society in the context of secular social sciences, striving to overcome utilitarianism. It was the "civil economy" movement, however, that exercised greatest influence on Benedict XVI's encyclicalCaritas in Veritatebr> This present volume reflects on the general scope of these notions for business and society. This is done by structuring the book in two parts, each dedicated to one of the two concepts. Each part has two general chapters and two that apply the notions to business and to business education. The authors are a mix of well-known emeritus professors and younger talented emerging scholars. We have also been careful to combine European with American authors. A Catholic Spirituality for Business: The Logic of Gift does not seek to provide a definitive answer to all social challenges, but to make a contribution to a better understanding of Christian spirituality and gift in connection with business organizations. The authors in this book are convinced that markets can be ethical and social, that moral change towards ethical capitalism is possible.